The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.21203/rs.3.rs-570505/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sildenafil for idiopathic pulmonary fibrosis: A systematic review and meta-analysis

Abstract: Background: Patients with idiopathic pulmonary fibrosis have a poor overall prognosis and there are few evidence based drug therapies that reduce mortality. Objective: This systematic review and meta-analysis aims to assess whether sildenafil reduces mortality, reduces disease progression and the adverse side effects associated with it. Methods: In this review, randomized controlled studies (RCTs) were retrieved from MEDLINE, Cochrane, and EMBASE. The primary outcome was mortality. The secondary outcomes inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Thus, their data suggest that PDE5i might improve survival in patients with ILD and severe PH and that an individualized trial of PDE5i (with continuation in those who respond) is a reasonable approach in expert PH centres (Figure 1). Clinicians following this approach might be reassured by a meta‐analysis of the aforementioned sildenafil trials, which suggested a potential mortality benefit in the overall IPF population and an unlikely signal for harm 12 . However, given the limitations and biases inherent to retrospective observational analyses and issues arising from the populations included in the previous trials of PDE5i in ILD, we wish to underscore the need for a future randomized placebo‐controlled trial of PDE5i in a population enriched for severe PH, and possibly stratified by the presence of RV dysfunction at baseline.…”
Section: Figurementioning
confidence: 99%
“…Thus, their data suggest that PDE5i might improve survival in patients with ILD and severe PH and that an individualized trial of PDE5i (with continuation in those who respond) is a reasonable approach in expert PH centres (Figure 1). Clinicians following this approach might be reassured by a meta‐analysis of the aforementioned sildenafil trials, which suggested a potential mortality benefit in the overall IPF population and an unlikely signal for harm 12 . However, given the limitations and biases inherent to retrospective observational analyses and issues arising from the populations included in the previous trials of PDE5i in ILD, we wish to underscore the need for a future randomized placebo‐controlled trial of PDE5i in a population enriched for severe PH, and possibly stratified by the presence of RV dysfunction at baseline.…”
Section: Figurementioning
confidence: 99%